Cold active lipases – an update. Issue 3 (2nd July 2016) - Kavitha, M.
ABSTRACT: Cold active lipases (CLPs) are gaining importance nowadays as they are increasingly used in fine chemical synthesis, bioremediation, food processing and as detergent additive. These enzymes exhibit high catalytic activity at low temperatures and flexibility to act at low water medium. Since they are active at low temperatures consume less energy and also stabilize fragile compounds in the reaction medium. CLPs are commonly obtained from psychrophilic microorganisms which thrive in cold habitats. Compared to mesophilic and thermophilic lipases, only a few CLPs were studied and industrially exploited so far. CLPs ( C. antarctica lipase-A and C. antarctica lipase-B) from Candida antarctica isolated from Antarctic region are the well studied and industrially employed, and many are being followed up. This review updates the CLPs reported recently and the industrial applications of CLPs.